2013
DOI: 10.1128/aac.01585-13
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-Induced Autoactivation of IS 256 in Staphylococcus aureus

Abstract: The 3= end of rsbU, encoding the positive regulator of the stress factor sigma B, was identified as a hot spot for spontaneous IS256 insertion in Staphylococcus aureus SA137/93G. Interestingly, subinhibitory concentrations of chloramphenicol in combination with heat stress, as well as linezolid and spectinomycin at physiological temperatures, selected for such rsbU:: IS256 insertion mutants. In consequence of the inactivation of rsbU, the IS256 transposition frequency was increased 4-fold in S. aureus HG001. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 29 publications
1
16
0
2
Order By: Relevance
“…Multiple IS256 transpositions have been observed in the genome of S. aureus and correlated with reduced susceptibility to vancomycin, as a copy of IS256 was found in the promoter region of genes associated with glycopeptide resistance originating hybrid promoters, probably responsible for an increased gene expression [ 34 ]. Other studies have also shown that exposure to antibiotics such as CIP, vancomycin, chloramphenicol, linezolid and spectinomycin activates spontaneous transposition of IS256 which could be associated with a decrease of antibiotic susceptibility [ 35 37 ]. Moreover, it has been shown that IS256 insertion in the promoter regions of the genes mecA in Staphylococcus sciuri [ 38 ] and llm in S. aureus [ 39 ] is involved in higher transcription rates of both genes with a concomitant increased resistance to methicillin.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple IS256 transpositions have been observed in the genome of S. aureus and correlated with reduced susceptibility to vancomycin, as a copy of IS256 was found in the promoter region of genes associated with glycopeptide resistance originating hybrid promoters, probably responsible for an increased gene expression [ 34 ]. Other studies have also shown that exposure to antibiotics such as CIP, vancomycin, chloramphenicol, linezolid and spectinomycin activates spontaneous transposition of IS256 which could be associated with a decrease of antibiotic susceptibility [ 35 37 ]. Moreover, it has been shown that IS256 insertion in the promoter regions of the genes mecA in Staphylococcus sciuri [ 38 ] and llm in S. aureus [ 39 ] is involved in higher transcription rates of both genes with a concomitant increased resistance to methicillin.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, bone sialoprotein-binding protein (Bbp) and collagen adhesin (Cna) play a crucial role in the onset of device-related infections (Arciola et al, 2005b ; Xu et al, 2005 ; Campoccia et al, 2009 ; Vazquez et al, 2011 ; Post et al, 2014 ). S. aureus can also yield a variety of other virulence factors, such as Panton-Valentine leukocidin (PVL), often associated with necrotizing pneumonia and skin infections (Rasigade et al, 2011 ), toxic shock syndrome toxin (TSST), a super-antigenic toxin more common in MSSA lineages (He et al, 2013 ), and the insertion sequence IS 256 , widespread in genomes of multi-resistant staphylococci (Byrne et al, 1989 ; Depardieu et al, 2007 ; Schreiber et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bursts in IS transposition have been reported to be associated with harsh environmental conditions [ 45 , 48 , 50 ]. As an example, antibiotic treatment results in an increased frequency of IS transposition which may accelerate the development of resistance [ 33 , 52 ]. Under our model, strong transposition bursts increase the mean fitness of organisms through selection of beneficial mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of IS transposition is often suppressed through such negative regulation [ 3 ]. The release from regulation of IS transpositions in response to environmental challenges has been observed [ 33 , 45 , 47 52 ]. We call this elevation of the transposition rate a transposition burst .…”
Section: Introductionmentioning
confidence: 99%